Kempner-like Harmonic Series - Allouche, Jean-Paul; Morin, Claude (The American mathematical monthly, 2024)
Inspired by a question asked on the list mathfun, we revisit Kempner-like series, i.e., harmonic sums...1/n where the integers n in the summation have "restricted" digits. First we give a short proof that limk→∞(... = 2 log 2, where s2(n) is the sum of the binary digits of the integer n. Then we give a generalization that addresses the case where s2(n) is replaced with sb(n), the sum of b-ary digits in base b: we prove that limk→∞... = (2 log b)/(b − 1). Finally we indicate that other generalizations could be studied: the sum of digits in base 2 could be replaced with, e.g., the function a11(n) of -possibly overlapping- 11 in the base-2 expansion of n, for which one can obtain limk→∞... 1/n = 4 log 2. (ProQuest: ... denotes formulae omited.)